Assessment Of Communicative Qualities Of Primary Class Teachers - Hulkar Mirabidovna Mirkosimova (Euro Asian Journal Publishing, 2024)
The article examines the influence of the guiding communicative qualities of primary school teachers on the development of a democratic, authoritarian and liberal service personality. Psychologist of research work on ensuring the communicative qualities of primary school students
Keywords: pedagogical communication; democratic; authoritarian; liberal